The Effect of Student Engagement on Boarding School Students' Online Learning Achievement - Mulyadi; Omika, Hefri Asra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
Boarding school students must participate in online learning due to the COVID-19 pandemic. Student engagement is an important aspect that must be considered in online learning. This study aims to determine: (1) the level of student engagement of boarding school students, (2) to investigate the effect of simultaneous behavioral engagement, emotional engagement, and cognitive engagement on learning achievement, and (3) to determine the relationship between behavioral, emotional and cognitive engagement with learning achievement, (4) to measure the relative and effective contribution of behavioral, emotional and cognitive engagement on learning achievement. This research is quantitative research with an ex post facto type. 182 boarding school students participated in this study. The data collection instrument used is the engagement scale from Fredricks & McCloskey. Data processing using descriptive and inferential statistics. The inferential test used is multiple linear regression and Pearson correlation. This study’s results indicate a significant influence between behavioral, emotional, and cognitive engagement on the learning achievement. The influence of these three variables on learning achievement is 46.7%. While the results of the correlation test showed that there is a significant relationship between the variables of behavioral, emotional, and cognitive engagement in learning achievement.